Efektivitas Data-Driven Instruction Terhadap Motivasi Belajar Siswa Sekolah Dasar Dalam Pembelajaran IPA - Emi Azwarina; Erviana Dewi; Nurhalizah Putri (PGSD UNU NTB, 2025)
This study aims to analyze the effectiveness of data-driven instruction in improving elementary school students' learning motivation in Natural Science learning. The study used a quantitative approach with an experimental method and a pretest-posttest control group design. The subjects were fourth or fifth grade students divided into an experimental group and a control group. Data were collected through a learning motivation questionnaire, observation, and documentation. Data analysis included normality tests, homogeneity tests, t-tests, and effect size calculations. The results showed a significant increase in learning motivation in the experimental group compared to the control group. The increase was seen in aspects of student interest, attention, persistence, and self-confidence. Observations also showed that students were more active and involved in the learning process. The use of digital media such as Wordwall and Quizizz strengthened engagement through interactive and feedback-based presentations. These findings indicate that data-driven instruction can create adaptive and responsive learning to student needs. This approach is effective in increasing learning motivation as well as the quality of interactions in science learning. Therefore, this strategy is relevant for implementation in learning in the digital era.